ANALISIS PEMBUATAN DODOL BERBAHAN BAKU TEPUNG MELINJO DAN TEPUNG BERAS KETAN - Alyanti, Alyanti; Patang, Patang; Nurmila, Nurmila (Universitas Negeri Makassar, 2017)
The study was aimed to determine the influence of melinjo flour substitution on the contents of protein, fat, ash, water, and carbohydrates in dodol melinjo and to determine the acceptance of the panelists on dodol melinjo based on the organoleptic test results. A Completely Randomized Design (CRD) was applied in this study using formulation such as K treatment (0% melinjo flour and 100% glutinous rice flour), A treatment (75% melinjo flour and 25% glutinous rice flour), B treatment (60% melinjo flour and 40% glutinous rice flour), and C treatment (50% melinjo flour and 50% glutinous rice flour). The result show that the best proximate test was resulted in C treatment with the same amount concentration between melinjo flour and glutinous rice flour.